First Experience Using 4‐Dimensional Hysterosalpingo‐Contrast Sonography With SonoVue for Assessing Fallopian Tube Patency. (1st July 2013) - He, Yanni; Geng, Qiang; Liu, Hongmei; Han, Xiaohua
Abstract : This study was conducted to describe our first experience using transvaginal 4‐dimensional (4D) hysterosalpingo‐contrast sonography with SonoVue (Bracco International BV, Amsterdam, the Netherlands) for diagnosis of fallopian tube patency. The study was prospective and conducted in a university hospital setting. The sonographic procedures included 2‐dimensional transvaginal sonography for evaluating uterine and ovarian mobility, observing intubation, and determining the initial plane and 4D hysterosalpingo‐contrast sonography for observing periovarian and pelvic diffusion. Ninety‐six outpatients visiting infertility clinics underwent 4D hysterosalpingo‐contrast sonography. All patients finished the examination successfully. A total of 192 fallopian tubes were assessed, of which 95 (49.5%) were classified as type A (the tube was patent, and the contrast agent flowed smoothly through it), 72 (37.5%) as type B (the tube was patent, but the contrast agent did not flow smoothly inside it), and 25 (13.0%) as type C (blocked). Sixteen patients underwent laparoscopy or laparoscopy combined with hysteroscopy; 28 tubes (87.5%) were concordant with laparoscopy. The sensitivity, specificity, positive predictive value, negative predictive value, and Youden index for 4D hysterosalpingo‐contrast sonography versus laparoscopy were 81.8%, 90.5%, 81.8%, 90.5%, and 0.72 respectively. In total, 92.7% of patients did not require a hospital stay after 4D hysterosalpingo‐contrast sonography, and none need resuscitation. The others stayed in the hospital for clinical observation because of a severe vasovagal reaction or severe pain but received only bed rest without any medical treatment. Forty patients (41.7%) felt slight pain; 39 (40.6%) felt moderate pain; and 15 (15.6%) had a vasovagal reaction. No procedure or postprocedure complications occurred in any patient. In conclusion, 4D hysterosalpingo‐contrast sonography with SonoVue is an available screening method for assessment of tubal patency and is tolerable for most patients.